Essentials of Genetics - Klug, William S Cummings, Michael R (Pearson, 2007)
Intended for courses in genetics found in biological sciences, agriculture, forestry, and health sciences, this work presents an overview of the discipline with coverage of both classical and modern genetics. It includes experiments and applications illustrating the nature of scientific discovery.